2022
DOI: 10.52965/001c.38241
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy Regret or Lack Thereof

Abstract: Background Vasectomy is a procedure that results in permanent yet reversible sterility and remains a great contraceptive option for many. Previous research studies have highlighted frequency of vasectomy utilization, defining characteristics of individuals who opt for this method, various surgical techniques, and the risks and benefits associated with the procedure. What remains to be defined is why or why not individuals may experience post-vasectomy regret and whether the previous characteristics correlate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our findings indicate that not only were childless and partnerless men were more likely to seek vasectomy post-Dobbs, but also these childless men were also more likely to be younger. Studies have demonstrated that vasectomy regret rate is approximately 4%–6% among men who undergo this procedure ( Anderson et al, 2022 ; Charles et al, 2023 ). Key social and demographic factors to be considered include age at time of procedure, parental status, and partner status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that not only were childless and partnerless men were more likely to seek vasectomy post-Dobbs, but also these childless men were also more likely to be younger. Studies have demonstrated that vasectomy regret rate is approximately 4%–6% among men who undergo this procedure ( Anderson et al, 2022 ; Charles et al, 2023 ). Key social and demographic factors to be considered include age at time of procedure, parental status, and partner status.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to compare vasectomy consultation and completion trends 1 year pre- and post-Dobbs specifically in childless and partnerless men, as this population may be more vulnerable to postprocedural regret ( Anderson et al, 2022 ; Charles et al, 2023 ). Consequently, this may result in additional reversal procedures and health care costs ( Pavlovich & Schlegel, 1997 ).…”
Section: Introductionmentioning
confidence: 99%